Transformative change through events business: a feminist ethic of care analysis of building the purpose economy. Issue 11 (2nd December 2021) - Higgins-Desbiolles, Freya; Monga, Manjit
Abstract: As we confront social, ecological and economic challenges, some look to a new model described as the purpose economy as a pathway to more sustainable and just futures. Responsible and sustainable events are increasingly of interest to both academics and practitioners. However, little work has explored the capacities for social entrepreneurship in events management and ways that events can build socio-cultural well-being. This article presents a case study of an unusual events business known as GOGO Events located in Adelaide, South Australia. For some eight years, GOGO has offered a social enterprise initiative training and supporting teams of marginalised people to create and install event installations. To accomplish this, GOGO's founder has built a web of stakeholders, including: corporate clients; not for profit organisations supporting homeless and vulnerable people; and these vulnerable people themselves. Together they build networks of care and social change. Using the lens of feminist care ethics, we analyse how such work contributes to building the purpose economy. These efforts move beyond corporate social responsibility and suggest events businesses can help build community, create relationships of care and contribute to more sustainable and fair futures. After COVID-19, such socially committed work has become even more imperative.